Determination of kappa Casein Gene Polymorphisms and Their Effects on Milk Composition in Some Native Cattle Breeds of Turkey - Gurses, Murad; Yuce, Huseyin (Medwell Online, 2012)
Polymorphisms in exon IV of bovine kappa-casein gene (CSN3) determine eleven allelic variants (A, B, C, E, F1, F2, G1, 02, H, I and J) for the gene. These variants are effective on milk production traits. The aim of this study was to detect kappa-casein polymorphisms in Anatolian Black (AB) and East Anatolian Red (EAR) native cattle breeds of Turkey. For this purpose, blood and milk samples were collected from Middle and East Anatolian region of Turkey. Milk samples were analyzed for protein, fat, lactose, solids, solids-not-fat content and density by using milk analyzer. After DNA was extracted from the blood samples, exon IV of CSN3 gene was amplified by PCR. PCR products were digested with HindIII and HaeIII enzymes to distinguish allelic variants A, B and E. Genotype frequencies were determined as AA = 0.500, AB = 0.500 for Anatolian Black and AA = 0.567, AB = 0.433 for East Anatolian Red. Allele frequencies were determined as A = 0.750, B = 0.250 for Anatolian Black and A = 0.783, B = 0.217 for East Anatolian Red. The effects of genotypes on milk protein and SNF contents were found significant in EAR (p<0.05) and also found close to significant in AB (p<0.1). The association between CSN3 genotypes and milk composition suggests that CSN3 polymorphism might be a useful marker for genotypic selection such as marker assisted selection. Selection of B allele for CSN3 polymorphism could provide considerable economic advantage for increasing milk quality.
Keywords: Native cattle breeds; kappa casein (CSN3); gene polymorphism; milk composition; enzymes